Reanalysis of the Rituximab in ANCA-Associated Vasculitis trial identifies granulocyte subsets as a novel early marker of successful treatment. Issue 1 (December 2015) - Nasrallah, Mazen; Pouliot, Yannick; Hartmann, Bjoern; Dunn, Patrick; Thomson, Elizabeth; Wiser, Jeffrey; Butte, Atul
Abstract Introduction In the present study, we sought to identify markers in patients with anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) that distinguish those achieving remission at 6 months following rituximab or cyclophosphamide treatment from those for whom treatment failed in the Rituximab in ANCA-Associated Vasculitis (RAVE) trial. Methods Clinical and flow cytometry data from the RAVE trial were downloaded from the Immunology Database and Analysis Portal and Immune Tolerance Network TrialShare public repositories. Flow cytometry data were analyzed using validated automated gating and joined with clinical data. Lymphocyte and granulocyte populations were measured in patients who achieved or failed to achieve remission. Results There was no difference in lymphocyte subsets and treatment outcome with either treatment. We defined a Granularity Index (GI) that measures the difference between the percentage of hypergranular and hypogranular granulocytes. We found that rituximab-treated patients who achieved remission had a significantly higher GI at baseline than those who did not (p  = 0.0085) and that this pattern was reversed in cyclophosphamide-treated patients (p  = 0.037). We defined optimal cutoff values of the GI using the Youden index. Cyclophosphamide was superior to rituximab in inducing remission in patients with GI below −9.25 % (67 % vs. 30 %, respectively;p  = 0.033), whereas rituximab was superior to cyclophosphamide for patients with GI greater than 47.6 % (83 % vs. 33 %, respectively;p  = 0.0002). Conclusions We identified distinct subsets of granulocytes found at baseline in patients with AAV that predicted whether they were more likely to achieve remission with cyclophosphamide or rituximab. Profiling patients on the basis of the GI may lead to more successful trials and therapeutic courses in AAV. Trial registration ClinicalTrials.gov identifier (for original study from which data were obtained):NCT00104299 . Date of registration: 24 February 2005.